The Influence of Work Culture, Motivation and Discipline on Personnel Performance of the Detention and Evidence Sub-Division of the Operational Section of the Special Detacle 88 Anti-Terror Police of the Republic of Indonesia - Yul Kuswoyo; Zulkifli Rangkuti; Eddy Hermawan Hasudungan Panjaitan (Dinasti Publisher, 2026)
Personnel performance is a strategic factor in supporting the effectiveness of operational tasks, especially in the Detention and Evidence Sub-Division of the Operational Section of the Special Detachment 88 Anti-Terrorism Police of the Republic of Indonesia which has a high level of risk and demands for professionalism. This study aims to analyze the influence of work culture, motivation, and discipline on personnel performance, both partially and simultaneously. This study uses a quantitative approach with the support of qualitative data as a complement to enrich the interpretation of the research results. Quantitative data were collected through a structured questionnaire, while qualitative data were obtained from open-ended statements in the questionnaire and short interviews with related informants. The study population was 122 personnel, with a sample of 94 respondents determined using sampling techniques tailored to the research needs. Data analysis was carried out using SPSS Version 27 software. The results of the study indicate that partially motivation and discipline have a positive and significant effect on personnel performance, while work culture does not show a significant effect on personnel performance. Simultaneously, work culture, motivation, and discipline contribute to personnel performance, with a coefficient of determination (R Square) of 0.434. This indicates that 43.4% of the variation in personnel performance can be explained by these three variables, while the remaining 56.6% is influenced by other factors outside the research model. These findings confirm that increasing motivation and consistently enforcing discipline are key factors in improving personnel performance, while work culture requires strengthening and adjustments to have a more significant impact on performance within the Special Detachment 88 Anti-Terror Police environment